English Education Master Students' Attributional Beliefs in Their Academic Reading Venture - Kristian Florensio Wijaya (Pascasarjana Universitas Negeri Makassar, 2021)
ABSTRACT To breed more successful, tenacious, and proficient L2 academic readers, the precise conceptions of attributional beliefs should be introduced earlier at the commencement of the L2 academic reading venture to better assist them in coping with a wide variety of academic reading learning issues potentially quenched their potent reading learning endeavor. Specifically, adaptive attributional beliefs played an important role in this academic learning arena since graduate university EFL learners will accurately attribute their reading learning success and failure as the minimum expendable efforts rather than lack of learning competencies along with luck. This present qualitative study aimed to investigate English Education Master Students’ attributional beliefs in their academic reading venture. One research problem was enacted in this study namely, what are the specific attributional beliefs upheld by English Education Master Students while engaging in the academic reading venture? Qualitative content analysis was harnessed in this study to yield a set of renewable conceptions out of the tangible phenomenon. The suggestive findings succinctly recited that the full induction of adaptive attributional beliefs had enabled the participants to be more creative, innovative, independent, strategic, and competent L2 academic readers amid laborious academic reading learning enterprises. Keywords: attributional beliefs, adaptive attributional beliefs, English Education Master Students, qualitative content analysis